2015
DOI: 10.1021/pr501086e
|View full text |Cite
|
Sign up to set email alerts
|

Selenite-Induced Toxicity in Cancer Cells Is Mediated by Metabolic Generation of Endogenous Selenium Nanoparticles

Abstract: Selenite has been a touted cancer chemopreventative agent but generates conflicting outcomes. Multiple mechanisms of selenite cytotoxicity in cancer cells are thought to be induced by metabolites of selenite. We observed that intracellular metabolism of selenite generates endogenous selenium nanoparticles (SeNPs) in cancer cells. Critical proteins that bind with high affinity to elemental selenium during SeNPs self-assembly were identified through proteomics analysis; these include glycolytic enzymes, insolubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…13 Additionally, numerous studies have declared its chemopreventive and therapeutic activity against various types of cancers. [14][15][16][17] ALG is a natural ionic polymer with l-guluronate and d-mannuronate as major components. It is typically extracted from brown algae (Phaeophyceae).…”
Section: Introductionmentioning
confidence: 99%
“…13 Additionally, numerous studies have declared its chemopreventive and therapeutic activity against various types of cancers. [14][15][16][17] ALG is a natural ionic polymer with l-guluronate and d-mannuronate as major components. It is typically extracted from brown algae (Phaeophyceae).…”
Section: Introductionmentioning
confidence: 99%
“…When the dynamics of elemental Se were examined in lung cancer A549 cells by extended X-ray absorption fine structure (EXAFS), it was found that the levels of intracellular elemental Se increased between 4 and 72 h, and decreased slightly between 48 and 72 h. 15 As we have revealed that elemental Se in cancer cells presented as SeNPs, 10 we therefore propose that there is a dynamic process of the formation of endogenous SeNPs in cells. In this study, we report the dynamic equilibrium of endogenous SeNP assembly and disassembly in non-small lung cancer H157 cells.…”
Section: Introductionmentioning
confidence: 80%
“…These results agree with previous studies. 10,21 This growth inhibition is caused by apoptosis, demonstrated by analysis using flow cytometry. 21 …”
Section: Viability and Formation Of Endogenous Senps In Seleniteexposmentioning
confidence: 99%
See 2 more Smart Citations